Interpopulation differences in male reproductive effort drive the population dynamics of a host exposed to an emerging fungal pathogen. Issue 2 (26th October 2021) - Valenzuela‐Sánchez, Andrés; Azat, Claudio; Cunningham, Andrew A.; Delgado, Soledad; Bacigalupe, Leonardo D.; Beltrand, Jaime; Serrano, José M.; Sentenac, Hugo; Haddow, Natashja; Toledo, Verónica; Schmidt, Benedikt R.; Cayuela, Hugo
Abstract: Compensatory recruitment is a key demographic mechanism that has allowed the coexistence of populations of susceptible amphibians with Batrachochytrium dendrobatidis (Bd), a fungus causing one of the most devastating emerging infectious disease ever recorded among vertebrates. However, the underlying processes (e.g. density‐dependent increase in survival at early life stages, change in reproductive traits) as well as the level of interpopulation variation in this response are poorly known. We explore potential mechanisms of compensatory recruitment in response to Bd infection by taking advantage of an amphibian system where male reproductive traits are easy to quantify in free‐living populations. The Southern Darwin's frog Rhinoderma darwinii is a vocal sac‐brooding species that exhibits a high susceptibility to lethal Bd infection. Using a 7‐year capture–recapture study at four populations with contrasting Bd infection status (one high prevalence, one low prevalence and two Bd‐free populations), we evaluated whether Bd‐positive populations exhibited a higher adult recruitment and a higher male reproductive effort than Bd‐negative populations. We also estimated population growth rates to explore whether recruitment compensated for the negative impacts of Bd on the survival of adults. In addition, we evaluated a potential demographic signal of compensatory recruitment (i.e. positive relationship between the proportion of juveniles and Bd prevalence) in response to Bd infection using raw count data from 13 R. darwinii populations. The high Bd prevalence population exhibited the highest male reproductive effort and the highest recruitment among the four monitored populations. This led to a growing population during the study period despite high mortality of adult hosts. In contrast, males from the population with low Bd prevalence had a low reproductive effort and this population, which had the lowest adult recruitment, was declining during the study period despite adults having a higher survival in comparison to the high Bd prevalence population. We also found a demographic signal of compensatory recruitment in response to Bd infection in our broader analysis of 13 R. darwinii populations. Our study underlines the importance of interpopulation variation in life‐history strategies on the fate of host populations after infectious disease emergence. Our results also suggest that an increase in reproductive effort can be one of the processes underlying compensatory recruitment in populations of Bd‐susceptible amphibians. Abstract : This study underlines the importance of intraspecific variation in life‐history strategies on the fate of host populations after infectious disease emergence. The results also suggest that an increase in reproductive effort can be one of the processes underlying compensatory recruitment in populations of chytridiomycosis‐susceptible amphibians.